Upregulation of Nucleotide-Binding Oligomerization Domain-, LRR- and Pyrin Domain-Containing Protein 3 in Motoneurons Following Peripheral Nerve Injury in Mice - Nógrádi, Bernát; Nyúl-Tóth, Ádám; Kozma, Mihály; Molnár, Kinga; Patai, Roland; Siklós, László; Wilhelm, Imola; Krizbai, István A. (Frontiers in Pharmacology, 2020)
Neuronal injuries are accompanied by release and accumulation of damage-associated molecules, which in turn may contribute to activation of the immune system. Since a wide range of danger signals (including endogenous ones) are detected by the NLRP3 (NOD-, LRR- and pyrin domain-containing protein 3) pattern recognition receptor, we hypothesized that NLRP3 may become activated in response to motor neuron injury. Here we show that peripheral injury of the oculomotor and the hypoglossal nerves results in upregulation of NLRP3 in corresponding motor nuclei in the brainstem of mice. Although basal expression of NLRP3 was observed in microglia, astroglia and neurons as well, its upregulation and co-localization with ASC (apoptosis-associated speck-like protein containing a CARD), suggesting inflammasome activation, was only detected in neurons. Injury-sensitive hypoglossal neurons responded with a more pronounced NLRP3 upregulation than injury-resistant motor neurons of the oculomotor nucleus. We further demonstrated that the mitochondrial protector diazoxide was able to reduce NLRP3 upregulation in a post-operative treatment paradigm. Our results indicate that NLRP3 is activated in motoneurons following acute nerve injury. Blockade of NLRP3 activation might contribute to the previously observed anti-inflammatory and neuroprotective effects of diazoxide.